ANALISIS PENGELOLAAN DAN KONTRIBUSI PENERIMAAN RETRIBUSI PELAYANAN KESEHATAN TERHADAP PENDAPATAN ASLI DAERAH DI KABUPATEN MINAHASA UTARA - Umbas, Brigita R.; Nangoi, Grace B.; Tirayoh, Victorina (Universitas Sam Ratulangi, 2018)
Health service levies are contributions to forced governments and direct return services can be appointed.This study has the aim of analyzing the management and contribution of receipts of health service fees by using a qualitative approach from secondary data available in the Regional Revenue Service of North Minahasa Regency. From the results of the study it can be seen that the role, structure and development of North Minahasa District Health Service Levy in an effort to increase local revenue by 107% in 2017. In 2014 its contribution was only 1.47% and increased in 2017 to be more effective at 10%Keywords: Regional Original Revenue, Health Service Retribution, Effectiveness and Contribution